A Study on the Challenges and Advantages with regard to Online Teaching during Pandemic Situation of Self-financing College Teachers in Thrissur District - et. al., Kalarenjini.V, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
COVID19 is the abbreviation used for Corona Virus Disease, is a communicable disease which is caused by a newly found Corona Virus. Most common indications are fever, dry cough, and tiredness. The outbreak was first identified in December 2019 at Wuhan City in the country China. On 30th January 2020, The World Health Organization (WHO) proclaimed the outbreak as a Public Health Emergency with International importance and duly announced it as a pandemic on March 11th2020.In India, the first case of Covid19, which emanated from China, was set forth on 30th January, 2020 at Thrissur District in Kerala. On March 24th, The Prime Minister made a decree of nationwide lockdown for 21days, to stop spreading of the pandemic, which in turn had a great impact on the life of 1.3 billion people in India. Kerala government has announced shut down of all schools and colleges in Kerala due to the outbreak. Due to Lock down for the last few months, every people got affected all over the country. There were lots of Socio-Economic problems emerged due to Lock Down with various groups of people around the country. Education Sector was highly affected because of the immediate close down of schools and colleges. Since the lockdown has announced during the month of March, students and teachers were deeply confused of conducting exams and all. In the next academic year schools and colleges were started functioning with Online Classes using different platforms like Google Meet, Microsoft Teams, Zoom etc. and Offline classes using WhatsApp, YouTube Channels etc. When teachers in Self-financing Colleges are concerned, they are less paid in terms of salary and other emoluments as compared with the teachers in government aided colleges. Most of them are working on contract basis and this brings job insecurity to them. When the colleges started with Online mode of teaching, they have to bear with the situation as same as the government aided teachers but with lesser benefits. Some may face financial crisis and some may have increased their workload. They also got some kind of benefits with Online teaching. Even though, Online teaching has got so much of importance and benefits now a days, the entire academic sessions conducted through Online mode become a tough task for the teachers and students. Data connectivity is considered to be an important factor for the successful conducting of teaching through Online Mode. Thus, this research work tries to find out the challenges faced and the advantages of online teaching of Self-financing College teachers in Thrissur District during pandemic period.